Exploitation of bioactive molecules in the processing of microalgal biomass into biodiesel - Raposo, Ana Margarida Branco (2017)
Dissertação de mestrado, Biologia Molecular e Microbiana, Faculdade de Ciências e Tecnologia, Universidade do Algarve, 2017